2015
DOI: 10.1590/0103-8478cr20140841
|View full text |Cite
|
Sign up to set email alerts
|

Geostatistics applied to the study of the spatial distribution of Tibraca limbativentris in flooded rice fields

Abstract: Tibraca limbativentris (rice stem bug) is an insect highly injurious to the rice crop in Brazil. The aim of this research was to define the spatial distribution of the T. limbativentris and improve the sampling process by means of geostatistical application techniques and construction of prediction maps in a flooded rice field located in the "Planalto da Campanha" Region, Rio Grande do Sul (RS), Brazil. The experiments were conducted in rice crop in the municipality of Itaqui - RS, in the crop years of 2009/10… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
21
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(24 citation statements)
references
References 15 publications
(9 reference statements)
3
21
0
Order By: Relevance
“…In general, CV values are inversely proportional to average values, and higher infestation of insects tend to provide lower CV, as also reported by Riffel et al (2012) and Pazini et al (2015), studying the spatial variability of soybean defoliating caterpillars (Anticarsia gemmatalis and Pseudoplusia includes) and rice stalk stink bug (Tibraca limbativentris), respectively. High CV values are commonly associated with counting data, and reflects the variability of the number found point-to-point (Chiba et al 2010).…”
Section: Methodssupporting
confidence: 73%
See 4 more Smart Citations
“…In general, CV values are inversely proportional to average values, and higher infestation of insects tend to provide lower CV, as also reported by Riffel et al (2012) and Pazini et al (2015), studying the spatial variability of soybean defoliating caterpillars (Anticarsia gemmatalis and Pseudoplusia includes) and rice stalk stink bug (Tibraca limbativentris), respectively. High CV values are commonly associated with counting data, and reflects the variability of the number found point-to-point (Chiba et al 2010).…”
Section: Methodssupporting
confidence: 73%
“…Pazini et al (2015) also found high CVs (i.e., > 100%) in infestation data of stalk stink bug (Tibraca limbativentris) in rice fields. It shows that regardless of species, bedbugs have similar spatial pattern of distribution in the field.…”
Section: Methodsmentioning
confidence: 76%
See 3 more Smart Citations